65=36q+10

Rewrite the equation as 36q+10=65.

36q+10=65

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

36⋅5=(q+10)⋅6

Rewrite the equation as (q+10)⋅6=36⋅5.

(q+10)⋅6=36⋅5

Multiply 36 by 5.

(q+10)⋅6=180

Divide each term by 6 and simplify.

Divide each term in (q+10)⋅6=180 by 6.

(q+10)⋅66=1806

Cancel the common factor of 6.

Cancel the common factor.

(q+10)⋅66=1806

Divide q+10 by 1.

q+10=1806

q+10=1806

Divide 180 by 6.

q+10=30

q+10=30

Move all terms not containing q to the right side of the equation.

Subtract 10 from both sides of the equation.

q=30-10

Subtract 10 from 30.

q=20

q=20

q=20

Solve for q 6/5=36/(q+10)